Central place foraging drives niche partitioning in seabirds. Issue 11 (27th August 2020) - Jessopp, Mark; Arneill, Gavin E.; Nykänen, Milaja; Bennison, Ashley; Rogan, Emer
Abstract : When species coexist, it is expected that they will reduce competition through niche partitioning or spatial segregation. We investigated the importance of niche partitioning versus spatial segregation across a seabird community where food and foraging constraints vary seasonally. Spatial clustering of seabird density in the western Irish Sea occurred in both seasons, with hotspots of seabird occurrence significantly higher in summer (Moran's I: 0.29) than winter (Moran's I: 0.19). A positive correlation between seabird density and feeding guild richness suggested a role for niche partitioning in reducing competition. This correlation was significantly stronger in summer than winter (Z‐test, p < 0.05), suggesting that when foraging range is constrained during the breeding season, interspecific competition is reduced through increased niche partitioning. Reduced spatial clustering and weaker correlations between density and feeding guild richness in winter suggests that spatial segregation plays a greater role in reducing interspecific competition outside the breeding season. This study demonstrates the relative importance of niche partitioning and spatial segregation, highlighting niche partitioning as a response to constraints on foraging range during the breeding season.